Case report: Significant response of alpha-fetoprotein-producing gastric cancer from combined chemotherapy and immunotherapy - Da, Xue; Juan, Zhang; Zhijun, Hu; Zhongchuan, Lyu (Frontiers in Immunology, 2024)
Background Alpha-fetoprotein-producing gastric cancer (AFPGC) represents a particularly aggressive subtype of gastric carcinoma characterized by elevated rates of vascular invasion, lymphatic dissemination, hepatic metastasis, and an unfavorable clinical outcome. Treatment strategies for AFPGC have historically lacked specificity. Herein, a case is presented involving AFPGC in which the patient exhibited a notable response to combined anti-PD-1 antibody immunotherapy and SOX chemotherapy, potentially achieving a cure. This report marks the first application of this regimen in neoadjuvant therapy for AFP gastric cancer, followed by radical resection and postoperative adjuvant therapy. Case summary A 62-year-old male patient presented with persistent upper abdominal distension and discomfort lasting over 2 months. Initial investigations revealed markedly elevated serum alpha-fetoprotein (AFP) levels, and subsequent pathological examination confirmed the diagnosis of AFPGC via gastroscopy. Due to the patient’s condition, surgical resection was initially deemed unfeasible. Therefore, a chemo-immunotherapy regimen consisting of SOX chemotherapy and the PD-1 inhibitor tislelizumab was administered for 3 cycles. Following this, successful laparoscopic radical gastrectomy was performed. The treatment protocol was continued with an additional 3 cycles postoperatively. At the time of this case report, the patient maintained a good quality of life with no evidence of disease recurrence or adverse events. Conclusion The present report highlights a case of AFPGC where significant therapeutic success was achieved through a combined regimen of chemotherapy and immunotherapy, both before and after surgery. The use of anti-PD-1 antibody (tislelizumab) in combination with SOX regimen (S-1 and oxaliplatin) demonstrated effective treatment of AFPGC, potentially offering a curative approach. This approach represents a promising targeted therapy option for patients with AFPGC.